Effect of amphibian chytrid fungus (Batrachochytrium dendrobatidis) on apparent survival of frogs and toads in the western USA. (August 2019) - Russell, Robin E.; Halstead, Brian J.; Mosher, Brittany A.; Muths, Erin; Adams, Michael J.; Grant, Evan H.C.; Fisher, Robert N.; Kleeman, Patrick M.; Backlin, Adam R.; Pearl, Christopher A.; Honeycutt, R. Ken; Hossack, Blake R.
Abstract: Despite increasing interest in determining the population-level effects of emerging infectious diseases on wildlife, estimating effects of disease on survival rates remains difficult. Even for a well-studied disease such as amphibian chytridiomycosis (caused by the fungus Batrachochytrium dendrobatidis [Bd]), there are few estimates of how survival of wild hosts is affected. We applied hierarchical models to long-term capture-mark-recapture data (mean = 10.6 yrs, range = 6–15 yrs) from >5500 uniquely-marked individuals to estimate the effect of Bd on apparent survival of four threatened or endangered ranid frog species ( Rana draytonii, R. muscosa, R. pretiosa, R. sierrae ) at 14 study sites in California and Oregon (USA) and one bufonid toad ( Anaxyrus boreas ) at two study sites in Wyoming and Montana. Our models indicated that the presence of Bd on an individual reduced apparent survival of ranid frogs by 6–15% depending on species and sex. The estimated difference between toads with and without Bd was 19% for the Montana population and 55% for the Wyoming population; however, the 95% Credible Interval of these estimates included zero. These results provide evidence for negative effects of Bd on survival in wild populations even in the absence of obvious die-offs. Determining what factors influence the magnitude of the effects of Bd on wildlife populations is an important next step toward identifying management actions. These estimates of Bd effects are important for understanding the extent and severity of disease, whether disease effects have changed over time, and for informing management actions.